Basic directions of the use of the term security in constitutions of the CIS state-parties - V M Redkous (RUDN Journal of Law, 2009)
The article sets forth the contemporary practice of using the concepts security, national security, state security in constitutions of the CIS state-parties; singles out basic institutions using the above concepts.